PENGARUH PEMBERIAN ASI TERHADAP SOSIAL EMOSIONAL ANAK USIA 4-5 TAHUN DI TK NGUPAYA MINA DESA DADAP KECAMATAN JUNTINYUAT KABUPATEN INDRAMAYU TAHUN 2026 - Yasmin, Malikah; Hizriyani, Rina; Syarifudin, Aip (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This descriptive qualitative research aims to examine the practice of breastfeeding from a health perspective, describe the social emotional development achievements of children aged 4-5 years, and analyze the significant influence of breastfeeding on this development. Involving 48 mother respondents at TK Ngupaya Mina, data was collected through open questionnaires, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model through data reduction, presentation, and drawing conclusions. The results show that the respondents' breastfeeding practices are classified as very optimal, reflected in the high coverage of exclusive breastfeeding for a full six months, the duration of breastfeeding lasting up to two years, the implementation of breastfeeding patterns according to the child's request (on-demand), as well as strong support from husbands and families. Children's social emotional development shows diversity; aspects of trust, initiative, empathy and morality develop very well, but independence in eating and dressing as well as feelings of shyness or hesitation when appearing in public still require further stimulation. This research found that breast milk has a significant effect on the social emotional dimensions formed through emotional bonds, namely trust, initiative and empathy, which is in line with Bowlby's attachment theory. On the other hand, the ability to overcome shame and build independence is more determined by parents' parenting patterns after the breastfeeding period ends. Thus, breastfeeding is an important foundation but not the only determinant of a child's social and emotional success. Successful breastfeeding needs to be accompanied by appropriate psychosocial stimulation, especially independence training and providing opportunities for socialization from an early age, so that all social and emotional aspects of children can grow optimally in a holistic and sustainable manner.